TECHNOLOGY PROGRESS IN AUTOMOTIVE SECTOR IN TERM OF ECO-FRIENDLY AND ENERGY EFFICIENT VEHICLES (Journal of Technology and Operations Management, 2020)
This review paper was intended to visit the importance of sustaining the technology of eco- friendly vehicles. To understand the concept of eco-friendly we have first to understand the history of energy exploitation by human being. This review paper emphasize on the transition of energy source exploitation running thru early renaissance until the modern era we are in now. Internal Combustion Engine has served the world since early 20th century driving us into the new millennial that is the 21th century. The depletion of oil reserve indicate a utmost important for us to source for a new energy that we can exploit in abundant yet causes minimal effect to the environment. This review paper also brings in the concept of mature technology and how it can actually be a good thing that push us into innovating and creating new technology to be capable in adopting new ways in ensuring sustainability of humans by means of sustaining the technology.